2020
DOI: 10.1099/acmi.0.000105
|View full text |Cite
|
Sign up to set email alerts
|

Chalcones, stilbenes and ketones have anti-infective properties via inhibition of bacterial drug-efflux and consequential synergism with antimicrobial agents

Abstract: With antimicrobial resistance creating a major public health crisis, the designing of novel antimicrobial compounds that effectively combat bacterial infection is becoming increasingly critical. Interdisciplinary approaches integrate the best features of whole-cell phenotypic evaluation to validate novel therapeutic targets and discover new leads to combat antimicrobial resistance. In this project, whole-cell phenotypic evaluation such as testing inhibitors on bacterial growth, viability, efflux pump, biofilm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Previous studies have also indicated their bactericidal properties against various pathogenic microbial organisms [ 31 , 32 , 33 ]. Emerging studies have also indicated that chalcones and their derivatives prevent biofilm formation in bacterial colonies [ 34 , 35 , 36 ] and enhance antibiotic sensitivity [ 37 , 38 ]. The bacterial strains used are pathogenic to humans and animals as well as known to be lethal in many conditions [ 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have also indicated their bactericidal properties against various pathogenic microbial organisms [ 31 , 32 , 33 ]. Emerging studies have also indicated that chalcones and their derivatives prevent biofilm formation in bacterial colonies [ 34 , 35 , 36 ] and enhance antibiotic sensitivity [ 37 , 38 ]. The bacterial strains used are pathogenic to humans and animals as well as known to be lethal in many conditions [ 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the primary pharmacological intervention for treating bacterial-induced exacerbations is antibiotic therapy, which may reduce an individual’s frequency of exacerbations ( Ramos et al., 2014 ; Huckle et al., 2018 ) but overall, may increase the risk of resistant bacterial growth in patients ( Huckle et al., 2018 ). Polyphenols reduce bacterial antibiotic resistance mechanisms, such as drug efflux, and potentiate antibiotic efficacy ( Dey et al., 2015 ; Suriyanarayanan and Sarojini Santhosh, 2015 ), including compounds in the chalcone structural family in which phloretin belongs ( Ferraz et al., 2020 ; Hellewell and Bhakta, 2020 ). These results provide the basis for further studies to examine the ability of phloretin to improve bacterial-induced symptoms in COPD or to augment antibiotic therapy and potentiate its efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…ketones have demonstrated antibacterial effectiveness against a range of pathogens, including E. coli [5], Staphylococcus aureus [6], and Bacillus subtilis [7]. Notably, dibenzalacetone, a ketone compound widely utilized in cosmetic sunscreens [8], has also been identified for its antioxidant [9] and antileishmanial activities [10].…”
Section: Certainmentioning
confidence: 99%